2022
DOI: 10.5582/ddt.2022.01025
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of contezolid (MRX-I) against multidrug-resistant tuberculosis and extensively drug-resistant tuberculosis

Abstract: Tuberculosis has become a great global public health threat. Compared with drug-susceptible tuberculosis (TB), the treatment regimens for multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) involve more severe adverse events and poorer treatment outcomes. Linezolid (LZD) is the first oxazolidinones used for TB. Thanks to its potent activity against Mycobacterium tuberculosis, LZD has become one of the key agents in the regimens against MDR/XDR-TB. However, this drug m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Contezolid is a novel oxazolidinone drug designed to address the myelosuppression and MAO inhibition associated with linezolid. It can inhibit the formation of a functional 70S initiation complex required for bacterial replication and has a broad antibacterial spectrum against Staphylococcus, Streptococcus, Enterococcus, Mycobacterium tuberculosis, nontuberculous mycobacteria, and Nocardia (6,(9)(10)(11)(12). A number of studies (13)(14)(15) have confirmed the safety and tolerability of contezolid in healthy Chinese subjects, and a phase III clinical trial (16) in China showed that the incidence of hematological adverse events induced by contezolid during 7-14 days of treatment was significantly lower than that induced by linezolid.…”
Section: Discussionmentioning
confidence: 99%
“…Contezolid is a novel oxazolidinone drug designed to address the myelosuppression and MAO inhibition associated with linezolid. It can inhibit the formation of a functional 70S initiation complex required for bacterial replication and has a broad antibacterial spectrum against Staphylococcus, Streptococcus, Enterococcus, Mycobacterium tuberculosis, nontuberculous mycobacteria, and Nocardia (6,(9)(10)(11)(12). A number of studies (13)(14)(15) have confirmed the safety and tolerability of contezolid in healthy Chinese subjects, and a phase III clinical trial (16) in China showed that the incidence of hematological adverse events induced by contezolid during 7-14 days of treatment was significantly lower than that induced by linezolid.…”
Section: Discussionmentioning
confidence: 99%
“…MRX-I had a strong anti-Gram-positive bacterial ability with a similar efficacy to that of LZD, and the clinical cure rates of MRX-I and LZD were reported to be 93.0% and 93.4% at post-treatment visits, respectively, in a critical phase III study (CTR20150855) for the treatment of complex skin and soft-tissue infections in China which was conducted in 50 clinical centers ( 10 , 11 ). Besides, compared with LZD, MRX-I has more safety advantages, including tolerance and minimal adverse effects (such as hematological adverse events and myelosuppression) ( 12 ). Additionally, it has been reported that MRX-I exhibits anti- M .…”
Section: Observationmentioning
confidence: 99%
“…In contezolid, the A and B rings have a non-coplanar structure, which enhances the bacterial target binding, thus reducing the risk of drug resistance and killing bacteria more efficiently (4). It reduces the penetration of somatic cells and mitochondria, thus preserving the normal function of mitochondria and effectively reducing the side effects of myelosuppression (5). At present, it has completed phase III clinical trials in China and has been approved for marketing in China in 2021 (6).…”
Section: Introductionmentioning
confidence: 99%